Beyond the Alleged Contradictions: A Historical and Linguistic Harmonization of the Birth Narratives of Jesus in the Gospel of Matthew and Luke - Agus Arda Setiawan Telaumbanua; Yonatan Alex Arifianto (TELEIOS: Jurnal Teologi dan Pendidikan Agama Kristen, 2026)
The birth of Jesus Christ is a cornerstone of Christian teaching, serving as historical evidence and a solid foundation for theology, particularly regarding the chronological discrepancy between the reign of Herod the Great in the Gospel of Matthew and that of Quirinius in the Gospel of Luke. This article aims to critically and comprehensively analyze and compare the narratives of Christ’s birth in the Gospels of Matthew and Luke to demonstrate that the narrative differences are not contradictory but can be harmoniously understood in light of each author's historical context and theological intent. Furthermore, it seeks to contribute to biblical theology literature and enrich apologetic discourse in addressing the challenges of the digital age. A qualitative literature review was employed to examine the chronology and context of the Roman Empire at the time of Jesus’ birth. The results of the analysis indicate that the chronological differences in the two Gospels are not contradictions. Rather, they reflect the theological emphasis and intended audience of each author. Linguistically, the term πρῶτος in Luke 2:2 can be interpreted as “before,” and ἡμέραις in Matthew 2:1 refers to the reign of Herod the Great, which reinforces the historical accuracy of both Gospels. Support from Roman sources, the practice of the census under Augustus, and the rotation of Zechariah’s priestly duties reinforce the possibility that Jesus was born in 6 or 5 BC, during the final years of Herod the Great’s reign. Therefore, there is no basis for accusing the Gospels of contradiction